The First Mountain Man : Preacher's Carnage - Book 27 - Johnstone, William W.; Johnstone, J. A. (New York : Pinnacle Books, Kensington Publishing Corp., 2021)
"Preacher is no hired killer. When a wagon train is brutally ambushed on the Sante Fe Trail though, he cant say no to the St. Louis businessman willing to pay him for justice. Its not the stolen gold thats convinced Preacher to take the job And its not the missing body of one of the wagon trains crew, a prime suspect who may have plotted the ambush and taken off with the gold. No, its the suspects lovely fiance, Alita Montez. She believes her boyfriend is innocent -- and has run off to find him. Preacher cant abide the idea of a young woman alone on the Sante Fe Trail. If the Comanche dont get her, the coyotes will. And Preacher cant have that. But to save the girl and get the gold, the legendary mountain man will have to forge a path thats as twisted as a nest of rattlers, face off with trigger-happy kidnappers, backstabbers, and bounty-hunters -- and match wits with Styles Mallory, the biggest baddest frontiersman of them all ..."--Amazon.com.
Keywords: Preacher -- (Fictitious character) -- Fiction; Trappers -- Fiction; Mountain life -- Fiction; West (U.S.) -- History -- 19th century; Fiction; Western fiction; Historical fiction